Optimization of fermentation process and antioxidant activity analysis of pomegranate grape wolfberry compound fruit wine - CHEN Taotao, HAO Xiangshuai, ZHANG Yifan, XING Zhibin, LIAO Wanqin, CHEN Zhuoyuan, FEI Liyue, TANG Fengxian, CHENG Chifang (Zhongguo niangzao)
In this study, a pomegranate grape wolfberry compound fruit wine was prepared using pomegranate as raw material, grape and wolfberry as auxiliary materials, the fermentation conditions were optimized by single factor and response surface tests, and the physicochemical index and antioxidant activity were analyzed. The results showed that the optimal fermentation process conditions for the pomegranate grape wolfberry compound fruit wine were initial soluble solids content 24.5 °Bx, initial pH 3.8, yeast inoculum 0.05%, and fermentation time 59 h. Under these optimized conditions, the alcohol content, sensory score, soluble solid contents, total phenols, total flavonoids, total anthocyanins of the fruit wine were 8%vol, 92.43, 12 °Bx, 12.58 mg gallic acid equivalent (GAE)/ml, 260.05 mg rutin equivalent (RE)/ml, and 50.10 mg/L, respectively. The 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging capacities were 91.49% and 97.75%, respectively. Hydroxyl radical scavenging capacity and absorbance value were significantly increased (P<0.05), which were 43.08% and 2.28, respectively.